2017
DOI: 10.1364/oe.25.009689
|View full text |Cite
|
Sign up to set email alerts
|

Field measurements of SOP transients in OPGW, with time and location correlation to lightning strikes

Abstract: We monitored the state of polarization (SOP) of polarized light in an optical ground wire (OPGW) link located in North America using a test method and apparatus that measured Stokes space angular velocity and geographic location of SOP transients. We observed transients up to 5.1 Mrad/s and were able to correlate these events in both time and location to lightning strikes documented by the United States Precision Lightning Network (USPLN).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…RSOP of 10 Mrad/s could still be tracked by using the proposed two schemes. It is reported that the polarization rotation speed of SOP will be as fast as 5.4 Mrad/s in [5], and that means the proposed schemes can perfectly overcome this problem. And owing to faster convergence speed, it can be also seen that the polarization tracking speed of the RLS-NPCA is a little faster than that of the LMS-NPCA.…”
Section: Txmentioning
confidence: 99%
See 2 more Smart Citations
“…RSOP of 10 Mrad/s could still be tracked by using the proposed two schemes. It is reported that the polarization rotation speed of SOP will be as fast as 5.4 Mrad/s in [5], and that means the proposed schemes can perfectly overcome this problem. And owing to faster convergence speed, it can be also seen that the polarization tracking speed of the RLS-NPCA is a little faster than that of the LMS-NPCA.…”
Section: Txmentioning
confidence: 99%
“…However, computational complexity and power consumption of DSP algorithms in coherent detection are the most major concern for medium and short-reach applications. Furthermore, a polarization division multiplexing (PDM) coherent optical transmission system is usually limited by the ultrafast rotation of state of polarization (RSOP) [5], [6] and the time-varying laser phase noise. Therefore, a low-complexity and high-performance DSP algorithm is highly desired.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in-depth study performed using Verizon aerial fiber in [9,10] showed that aerial fibers typically encounter higher SOP transients than those buried in the ground. In [11], data were collected from an OPGW plant in order to determine the correlation between SOP transients and lightning strikes.…”
Section: Causes Of State-of-polarization Transientsmentioning
confidence: 99%
“…Based on the polarization characteristics of light, the PDM technology uses two orthogonal optical carrier polarization states to simultaneously propagate two signals, which can double the capacity of communication systems [7]. However, some factors such as mechanical vibration and extreme weather may lead to rapid changes of signal polarization state in a coherent optical communication system [8]. This type of signal effect is called the rotation of state of polarization (RSOP).…”
Section: Introductionmentioning
confidence: 99%